2020
DOI: 10.21037/hbsn.2019.06.11
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study to evaluate the prognostic value of different nutritional assessment scores in liver surgery: NURIMAS Liver (DRKS00006340)

Abstract: Background: Malnutrition is recognised as a preoperative risk factor for patients undergoing hepatic resection. It is important to identify malnourished patients and take preventive therapeutic action before surgery. However, there is no evidence regarding which existing nutritional assessment score (NAS) is best suited to predict outcomes of liver surgery.Methods: All patients scheduled for elective liver resection at the surgical department of the University Hospital of Heidelberg and the Municipal Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…(1) All the patients received routine examination. (2) e patients received indocyanine green excretive test with 15-minute retention and other methods to evaluate their liver function [7,8]. (3) e patients underwent imaging examinations, including MRI examination and ultrasound examination to observe the tumor size, location, and other information and to determine whether extrahepatic metastasis occurred.…”
Section: Preoperative Assessment Sixty Lc Patients Treated In Thementioning
confidence: 99%
“…(1) All the patients received routine examination. (2) e patients received indocyanine green excretive test with 15-minute retention and other methods to evaluate their liver function [7,8]. (3) e patients underwent imaging examinations, including MRI examination and ultrasound examination to observe the tumor size, location, and other information and to determine whether extrahepatic metastasis occurred.…”
Section: Preoperative Assessment Sixty Lc Patients Treated In Thementioning
confidence: 99%
“…In modern surgical operations, surgeons and researchers pay increasing attention to the role of nutritional status in the preoperative assessment, and malnutrition has been proven to be a risk factor for postoperative complications. 12 , 13 Sarcopenia, a malnutrition-related muscle disease characterized by low muscle strength, low muscle quantity and quality and poor physical performance, mainly occurs in older people and is possibly caused by disordered energy metabolism. 14 Several studies have reported that sarcopenia, myosteatosis, visceral adiposity and other malnutrition-related indicators play vital roles in the development of postoperative complications.…”
Section: Introductionmentioning
confidence: 99%
“…Malnutrition is considered to be a preoperative risk factor for adverse postoperative outcomes (8,9). Sarcopenia is also considered a malnutrition syndrome characterized by the progressive loss of skeletal muscle mass and strength and impaired muscular function that is caused by decreased protein synthesis and disturbed energy metabolism (10).…”
Section: Introductionmentioning
confidence: 99%
“…However, the impacts of the above factors on the postoperative complications of liver resection in HAE patients remain unknown. Furthermore, Pascal et al found that the existing nutritional screening tools did not show a good prediction ability of the postoperative complications of liver resection in a prospective study (9). Therefore, it is necessary to establish a new nutrition score using other methods to predict complications after liver resection for HAE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation